LEGAL ANALYSIS OF A HUSBAND'S LAWSUIT FOR DIVORCE AGAINST WIFE FOR NOT FULFILLING HER OBLIGATIONS STUDY OF RULING NO.824/PDT.G/2020/PN MEDAN: ANALISIS HUKUM TENTANG GUGATAN CERAI OLEH SUAMI TERHADAP ISTRI KARENA TIDAK MEMENUHI KEWAJIBANNYA STUDI PUTUSAN NO.824/PDT.G/2020/PN MEDAN - Petrus Sembiring, Sunardi (UPMI Proceeding Series, 2023)
Divorce is a breaking of the marriage bond between the two parties, namely the husband and wife due to the occurrence of an disharmony in family relations that is fractured on the basis of an internal factor or external factor that occurs. As with divorce issues that often end up in court, divorce that occurs will naturally have legal consequences for husband and wife, children and joint property. And to find out the factors causing the application for divorce at the Medan District Court. The type of research used in this thesis is a case study case decision No. 824/Pdt.G/2020/PN.Medan field research is research that uses secondary data obtained from books, laws . Journal, this research raises the problem which is the legal basis for judges, namely from (Article 39 Paragraph 1 Law Number 1 of 1974 as is the statutory system which is more underlying and used by judges in determining their decisions on the basis of judges' decisions regarding divorce. The results of this study indicate that divorce can occur because there is a legal basis on which the divorce is valid.